Good. I hope you get locked, most mainly banned. Nobody needs you, “FrIsK”
Answer:
option a
Step-by-step explanation:
i think this because my teacher in my business class stated this before to the whole class but I was distracted so it can totally be wrong if it is my bad
Answer:
3
Step-by-step explanation:
f(x) = 3x+1
f(x+h) = 3(x+h)+1 = 3x+3h+1
f(x+h) - f(x)= 3x+3h+1-3x-1 = 3h
3h/h=3
That is an interesting fact thank you for sharing your information
y = -0.60x - 4
because the slope stays the same because it is parallel and the y intercept for the new equation ends up being -4